Comparative survival of five porcine reproductive and respiratory syndrome virus strains on six fomites - Angie Quinonez-Munoz; Nader M. Sobhy; Sagar M. Goyal (Veterinary World, 2024)
Background and Aim: Despite the availability of vaccines, porcine reproductive and respiratory syndrome virus (PRRSV) continues to cause disease outbreaks in pigs worldwide. One of the reasons for this problem is the frequent mutation of the virus, which creates new variants. This study was conducted to determine the survival of five PRRSV strains on four non-porous and two porous fomites at 22–25°C (room temperature).